Voyage of discovery: exploring the collections of the Asian Library of Leiden University - Reeuwijk, Alexander (Leiden University Press, 2017)
The Asian Library of Leiden University houses the world renowned and extensive Asian collections. This includes the largest collection on Indonesia worldwide and some of the foremost collections on South and Southeast Asia, China, Japan and Korea.0'Voyage of Discovery' contains more than twenty essays of academics, curators and authors on various aspects of the collections. The book is richly illustrated and showcases twenty-five treasures from the Asian Library, including unique manuscripts and rare maps.0Alexander Reeuwijk is a writer with a focus on Asia, natural history and travel histories. His published books include works on the evolution theory, Indonesia and Iran